Dehydrofrozen mango slices a feasibility study - Valenton, Ma. Lourdes L.; Gatchalian, Miflo
The study was divided into two major phases. The first phase involved the determination of the drying temperature and pre-treatment method for the dehydrofreezing of mango slices and the second phase was concerned with storage studies. In the first phases, drying temperatures of 150°F and 180°F were tested on both blanched and unblanched mango slices. Objective and subjective tests were used to compare the physical and sensory characteristics of the products. A statistical analysis of panel mean scores showed better texture, flavor and general acceptability for the mangoes which were steam blanched and dried at 150°F. In the second phase, two batches of dehydrofrozen mango slices processed at the conditions established in Phase I were stored at two storage temperatures of -20°C and -8°C for 15 days. Statistical analysis showed better texture results of subjective and objective tests showed better texture and more satisfactory rehydration for samples stored at -2
Thesis (B.S.)--University of the Philippines, Quezon City.
Typesc
Keywords: Mango -- Preserva; Food -- Preserva